Dark Tetrad traits and self-concept domains - Đošan, Sanja; Dinić, Bojana M. (Psihološka istraživanja, 2022)
The aim of this research was to examine the relations between the Dark Tetrad traits (narcissism, psychopathy, Machiavellianism, and sadism) and six domains of self-concept (social, competence, affect, academic, family, and physical self-concept). On a sample comprised 210 participants (69.5% women), age between 18 and 78 years, the Serbian adaptations of the following instruments were applied: Short Dark Triad (SD3), Assessment of Sadistic Personality (ASP), and Multidimensional Self Concept Scale (MSCS). The results showed that narcissism is positively related to all domains of self-concept, and the other three dimensions of Dark Tetrad are negatively related to almost all domains of self-concept. The results of hierarchical regression analysis showed that narcissism had significant and positive effects in the prediction of all domains of self-concept, especially social and physical self, while psychopathy had significant negative effects in the prediction of all domains, especially social self. Machiavellianism had a negative contribution to the prediction of social, competence, and affect self-concept, while sadism had a negative contribution only to competence and academic self-concept. Although narcissism is considered as the „brightest“ dark trait, results could indicate that people with high scores of narcissism have biased evaluations of the self, which is in line with their grandiose and superior self-view.
Keywords: Dark Tetrad; Dark Triad; self-concept